Marcadores moleculares para a caracterização genética de Cereus peruvianus Mill. (Cactaceae) - Tavares, Juliana Sala de Faria (2011)
Cereus peruvianus is an ornamental cactus, popularly called "mandacaru" in Brazil, cultivated in gardens and in biological preservation areas. The species is ecologically, economically and industrially important due to the large number of compounds it can produce. Current research estimates the transferability of microsatellite markers of other cactus species to Cereus peruvianus and analyzes the species's genetic diversity. Genetic diversity/similarity has been estimated by Amplified Fragments Length Polymorphism (AFLP) markers in seedlings originated from seeds of different accesses collected at different locations in the states of Paraná, Piauí and São Paulo, Brazil. Thirty-three pairs of microsatellite primers developed from different cactus species were evaluated so that microsatellite markers could be characterized. Five pairs of microsatellite primers developed from Polaskia chichipe, Ariocarpus bravoanus and Echinocactus grusonii were chosen, giving a 15.15% transferability of these primers to C. peruvianus. One of the microsatellites (Pchi47) provided information for 2 loci in the genome and thus 6 microsatellite heterologous loci were evaluated in 13 C. peruvianus accesses. Mean polymorphism for the 13 accesses reached 62.82% and evaluated loci showed 17 alleles at an average of 2.83 alleles per locus. Analysis of genotype frequency suggests a segregation distortion for several loci in which their frequency failed to present a Hardy-Weinberg equilibrium distribution. Fis mean rate (0.4466) indicated a deficit of heterozygotes for the loci under analysis. Differential frequency of certain alleles in the different accesses produced high genetic differentiation (Fst = 0.4260) among them. Genetic diversity analysis of descendents seedlings of 17 C. peruvianus accesses collected at different sites in the state of Paraná, in Picos (in the state of Piauí) and Peruíbe (in the state of São Paulo) was undertaken with six AFLP primers combinations. This analysis showed 348 loci where 282 (81%) polymorphs were. Polymorphism reached 10.42% within the accesses. Nei's genetic differentiation coefficient (Gst=0.7938) and the coefficient from microsatellites showed a higher genetic diversity among the accesses than that withing themselves. This information corroborated the low gene flow (Nm=0.1299). The similarity between the 17 descendants of evaluated seedlings ranged between 0.6193 and 0.9494 and produced a three-group dendrogram, or rather, two groups were made up from different accesses collected in the state of Paraná, whereas the third one was formed by accesses collected in the state of Piauí. The access from the state of São Paulo did not belong to the above groups. Microsatellite and AFLP results suggest a speciation process of the genus Cereus. Consequently, plants that grow in the states of Piauí (Picos), São Paulo (Peruíbe) and Paraná may either be different species of the genus Cereus or a species undergoing a speciation process.